Strategi Peningkatan Daya Saing Produk Perikanan Desa Sukajadi melalui Pemasaran Digital - Rifiyanti, Hafizah; Purwandari, Nuraini; Prasetya, Yuli; Nasution, Taruna; Kristantini, Rr. Aryanti; Machdum, Dade Maulana; Handriyo, Ghanistantiono Dwi (Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
The abdimas (community service) activity on digital marketing for aquaculture products in Desa Sukajadi, Bogor, aimed to strengthen the capacity of local fish farmers and micro-entrepreneurs in facing digital era market challenges. This program was initiated due to limited market access and low digital literacy among the community. The activity involved 12 participants selected from local aquaculture groups. The implementation included three stages: preparation (coordination and material design), training (presentation and demonstration on social media, marketplace use, and product content creation), and evaluation (pre- and post-training questionnaires). The evaluation showed an increase of 75% in participants’ understanding of digital marketing concepts and practical skills in using online promotional tools. Participants were able to create social media content and digital product catalogs independently after the training. The program proved that digital marketing can be an effective strategy to expand market reach and enhance the competitiveness of local aquaculture products. Continuous mentoring is recommended to ensure sustainability and long-term benefits for the community.